Flexible labor markets and employee health - Ferrie, Jane E.; Westerlund, Hugo; Virtanen, Marianna; Vahtera, Jussi; Kivimäki, Mika (SJWEH Supplements, 2008)
Moves towards a more flexible labor market have focused research attention on the health effects of downsizing, temporary employment, and job insecurity. Most published research documents adverse effects on health, although null findings and direct associations have been observed. There is evidence that major downsizing is associated with poor mental health, medically certified sickness absence, and poor physical health, including cardiovascular disease mortality, among the survivors of downsizing. Recent research suggests that repeated exposure to personnel expansion also predicts sickness absence and hospitalization. There is strong evidence that job insecurity adversely affects psychological health and also evidence of increases in poor self-reported physical health, workplace injuries and accidents, sickness absence, and health service use. However, evidence of a link with disease and premature death remains limited. While temporary workers are initially selected for good health, they generally have poorer mental and physical health, including increased premature mortality, in the long term.
Keywords: downsizing; employee health; expansion; flexibility; flexible labor market; health; job insecurity; labor market; narrative review; review; temporary employment